Households’ acceptance of aﬀordable Islamic public-private housing co-operative model (IPHCM) in Malaysia - Abdul Razak, Dzuljastri; Bilal, Muhammad; Amin, Hanudin (EMERALD GROUP PUBLISHING LTD, 2020)
The purpose of this study is to examine the determinants inﬂuencing low- and middle-income households in accepting the Islamic public-private housing co-operative model (IPHCM) as an alternative to contemporary affordable public housing models in Malaysia.. The research is carried out using self administered questionnaires. Data are collected from low and middle-income house households dwelling in PPR projects in Kuala Lumpur and Selangor. It used the theory of planned behaviour (TPB) and partial least squares to analyze. The ﬁndings suggest that subjective norm and perceived consumer religiosity is the most inﬂuential determinants that affect behavioural intention of low-middle income households in accepting the IPHCM model. Attitude had a signiﬁcantly positive relationship with households’ behavioural intentions towards accepting the IPHCM model. The result of this study provide guideline for policymakers to understand the behavioural intention of low- and middle-income households in accepting newly developed models in affordable public housing in Malaysia